Organizational commitment, religiosity, and auditors’ responsibility for fraud detection - Damayanti, Ni Nyoman Sri Rahayu; Agustia, Dian (International Journal of Management and Sustainability, 2024)
The government auditor plays a crucial role in the oversight and prevention of fraudulent activities inside the government. The examination of elements that influence the auditor’s responsibilities in identifying fraud holds significant importance. This is also supported by previous literature, which states that there is quite a lot of understanding related to fraud behavior that has not been explored in the fields of accounting and auditing. This study aims to examine the influence of affective commitment, continuance commitment, normative commitment, and religiosity on the fraud detection responsibility of the auditor. The present study employed a quantitative methodology utilizing a survey-based research design. The participants in this research comprised a sample of 101 government auditors employed at the Audit Board of the Republic of Indonesia. The hypothesis was tested using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that affective commitment, continuance commitment, normative commitment, and religiosity have a positive influence on the auditor’s responsibility in detecting fraud. This study also confirms the Theory of Planned Behavior (TPB). This research contributes to the development of literature related to behavioral accounting, especially regarding fraud detection responsibility. The implication of this research is that it is important for the audit board, especially human resource management, to consider providing activities that can increase the organizational commitment and religiosity of auditors, which can then be used as motivation for auditors to increase their responsibility in detecting fraud.